SOCIOLINGUISTIC PROFILE TO ALGERIA’S LANGUAGE PLANNING AND POLICY - Baghzou, Sabrina (Université de M'sila, 2017)
Language education policies in Algeria changed according to the different historical and political periods Algeria went through. . Algeria’s language policies went through three main phases. The first phase is the colonial era which consists of an educational system dominated by the French language. The second phase represents the socialist-era called the nationalist transition whereas the third corresponds to the transition to the free economic market with less assertive arabisation policies. After the civil war and reconciliation the educational system knew some reforms planned to remedy the educational system in order to meet the needs of the country facing the challenges of globalization.
Keywords: Sociolinguistic- Profile –Language- Planning – Policy- Algeria